Legal Issues of Entitlement to Compensation on the basis of Grave Professional Judicial Error - Alan Bahaddin Abdulla Almudarris; Saman Khorsheed Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In the state of law, everyone is subject to the rule of law, including judges. The legislator has therefore acknowledged that the judge might be responsible in the case of making a grave professional judicial error during the performance of his judicial function. This responsibility is an exception to the principle which acknowledges the special immunity for judges; and for this reason, the legislator has set forth special rules to hold the judge accountable for those mistakes in a manner which does not lead to diminishing their independence and protects them from malice and defamation. On the contrary, setting out rules for holding judges accountable is aimed at protecting litigants from judges’ mistakes and safeguarding their rights to obtain a fair compensation for the damages caused by virtue of these errors. For this process is surrounded by some legal issues, this study is an attempt to shed some light on these problems, study them and tackling them by developing appropriate legal solutions through studying the relevant applicable legislation in Iraq and the Kurdistan Region – Iraq and by depending on the analytical descriptive approach.